ANALISIS TINGKAT KEPUASAN PASIEN RAWAT JALAN (Studi kasus pada pasien rawat jalan di RSUD Dr. M. Ashari Kabupaten Pemalang) - Yuni Lestari; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2017)
This research was to identify the level of outpatient satisfaction and what indicators needs to be prioritized to improving the services quality in Dr. M. Ashari Pemalang Hospitals. The author used a quantitative descriptive research type with a total sample of 100 patients who used outpatient services in Dr. M. Ashari Pemalang Hospital. This study used satisfaction measurement through 6 service dimensions such as tangible, reliability, responsiveness, assurance, empathy, and communication by comparing the performance of (X) and expectations (Y) which caused the satisfied or dissatisfied feeling. The results of this research indicated, there were two dimensions which were considered in determining of the patients satisfaction who had high expectation but in a low working performance level, so these could be said that less satisfied to unsatisfied. These two dimensions were: 1. Tangible, in which there are 4 sub dimensions, they are completeness of facilities and infrastructure, hospital cleanliness, comfort of the hospital, and the neatness of appearance employee; 2. Reliability, in which there are 4 sub dimensions, they are speed of services, appropriateness of care schedule,and the simplicity of services procedure. While of the sixth dimension that had a lowest level of satisfaction that were reliability dimension which got rated of performance level of 2,33 (unsatisfaction).